PENERAPAN METODE PEMBELAJARAN SOSIODRAMA UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SDN 003SUNGAI BAKAU KECAMATAN SINABOI - Nirmalawati '; Hendri Marhadi Marhadi; Gustimal witri witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :This research is motivated by low yields social studies students, with a grade average of 59.77. While the completeness criteria Minimum value (KKM) Mathematics is 65 Among the students who was 22 people only 10 students who achieve KKM with classical completeness 45%. This research is Classroom Action Research (CAR) conducted aims to improve learning outcomes IPS Elementary School fifth grade students 003 Sungai Bakau Kecamatan Sinaboi by applying learning methods sociodrama. Data collection instruments in this thesis is the teacher and student activity sheets and learning outcomes. This thesis presents the results obtained by studying the average learning outcome measures 59.77 before rising to 74,13dan at UH increased to 80 aktvitas teacher observations increased in each cycle, the first cycle with a percentage of 54.54% of cycle kurangdan category II increased by 90.90% with very good category. Student activity increased from 43.18% first cycle with either category, the second cycle increased by 81.81% with very good category. The results of the study in class V Elementary School 003 Mangrove River District of Sinaboi prove that the application of learning methods can improve learning outcomes sociodrama IPS 003 fifth grade students of SDN Sungai Bakau Kecamatan Sinaboi. Keywords: Sociodrama Method, IPS Learning Outcomes